2016
DOI: 10.1542/hpeds.2016-0080
|View full text |Cite
|
Sign up to set email alerts
|

Medically Hospitalized Patients With Eating Disorders and Somatoform Disorders in Pediatrics: What Are Their Similarities and Differences and How Can We Improve Their Care?

Abstract: A B S T R A C T OBJECTIVES:The purpose of the current study is to describe the demographic and clinical characteristics and health care use of medically hospitalized patients with eating disorders (ED) and somatoform disorders (SFD) in a pediatric setting and to use the findings to explore opportunities for improved care. METHODS:Retrospective chart reviews of 125 patients with SFD and 125 patients with ED (N 5 250) seen at a tertiary pediatric facility over a 12-and 19-month period, respectively. RESULTS:Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Our cohort had a median age of 14 years and was predominantly female (80.3%) and Caucasian (77.6%). This is analogous to the characteristics of a typical patient hospitalized for eating disorders or somatoform disorders (adolescent, white female) [29]. We found that 22.4% of our cohort had disordered eating, corroborating previous findings that chronic pain and disordered eating commonly co-occur in adolescents [1][2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 90%
“…Our cohort had a median age of 14 years and was predominantly female (80.3%) and Caucasian (77.6%). This is analogous to the characteristics of a typical patient hospitalized for eating disorders or somatoform disorders (adolescent, white female) [29]. We found that 22.4% of our cohort had disordered eating, corroborating previous findings that chronic pain and disordered eating commonly co-occur in adolescents [1][2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 90%
“…The treatment of SSRDs can be initiated within the hospital setting with the goal of improving functionality and successfully transitioning to outpatient care. 35 Children with more profound and pervasive functional impairment, with or without other comorbid conditions, may need more intensive treatments, including admission to medical-psychiatric programs or physical rehabilitation units. 6 Disposition planning is multidisciplinary with a focus on promoting active engagement with the primary care provider (PCP), establishing follow-up care with outpatient mental health providers who are familiar with SSRDs, ongoing monitoring by subspecialty pediatric providers as indicated, using continued outpatient rehabilitative services if needed, and providing guidance to families and schools.…”
Section: Discussionmentioning
confidence: 99%
“…6 Disposition planning is multidisciplinary with a focus on promoting active engagement with the primary care provider (PCP), establishing follow-up care with outpatient mental health providers who are familiar with SSRDs, ongoing monitoring by subspecialty pediatric providers as indicated, using continued outpatient rehabilitative services if needed, and providing guidance to families and schools. 10,32,33,35,36 Scheduled and frequent follow-up visits with a PCP are important to maintain the alliance and investment in treatment and provide ongoing medical education and reassurance. 33 Limitations and Future Directions…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective chart review comparing pediatric patients with SSRD and eating disorders found that patients with EDs had longer medical admissions, more depressive disorders, suicidal ideation, and self-harm, whereas patients with SSRDs had greater utilization of emergency department and hospital services, and higher rates of learning difficulties and trauma ( Ibeziako et al, 2016 ). However, no study to date has compared SSRDs to ARFID specifically, differentiated from other eating disorder subtypes.…”
Section: Introductionmentioning
confidence: 99%